2019
DOI: 10.1002/sctm.19-0185
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplant tolerance associated with remote autologous mesenchymal stromal cell administration

Abstract: Here we report the case of successful immune tolerance induction in a living‐donor kidney transplant recipient remotely treated with autologous bone marrow‐derived mesenchymal stromal cells (MSC). This case report, which to the best of our knowledge is the first in the world in this setting, provides evidence that the modulation of the host immune system with MSC can enable the safe withdrawal of maintenance immunosuppressive drugs while preserving optimal long‐term kidney allograft function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Long-term follow-up highlighted a sustained increase in the ratio between Treg and CD8 + effector T cells in one of these patients, which was associated with a B-cell profile consistent with the pro-tolerogenic signature identified in other cohorts of spontaneously tolerant kidney transplant recipients ( 129 ). This patient consented to gradual tapering of immunosuppression, which was successfully completed without any evidence of rejection (the patient has been off immunosuppression for over two years), thus supporting the hypothesis that a single administration of MSC may induce a long-term, self-sustaining immunoregulatory process responsible for tolerance induction ( 130 ). Other groups reported similar immunomodulating effects after the administration of autologous BM-MSC, which were safe and induced an increase in Treg frequency and a reduction in T-cell proliferation ( 131 ); nevertheless, so far immunosuppression withdrawal has not been attempted in any other study on renal transplant recipients.…”
Section: Introductionsupporting
confidence: 52%
“…Long-term follow-up highlighted a sustained increase in the ratio between Treg and CD8 + effector T cells in one of these patients, which was associated with a B-cell profile consistent with the pro-tolerogenic signature identified in other cohorts of spontaneously tolerant kidney transplant recipients ( 129 ). This patient consented to gradual tapering of immunosuppression, which was successfully completed without any evidence of rejection (the patient has been off immunosuppression for over two years), thus supporting the hypothesis that a single administration of MSC may induce a long-term, self-sustaining immunoregulatory process responsible for tolerance induction ( 130 ). Other groups reported similar immunomodulating effects after the administration of autologous BM-MSC, which were safe and induced an increase in Treg frequency and a reduction in T-cell proliferation ( 131 ); nevertheless, so far immunosuppression withdrawal has not been attempted in any other study on renal transplant recipients.…”
Section: Introductionsupporting
confidence: 52%
“…As mentioned above, it was demonstrated that timing of MSC infusion was of importance as an engraftment syndrome with infiltration of immune cells and C3 deposits were found when MSC were administered at 7 days after kidney transplantation, which was not observed when MSC were given before transplantation [24]. Moreover, an interesting case provided evidence that in a renal transplant recipient, infusion of autologous bone marrow MSC was associated with safe complete discontinuation of maintenance immunosuppression after transplantation allowing a state of immune tolerance [36]. Progression of the field is also influenced by logistic and regulatory issues, which accompany cell‐based therapy such as clinical grade cell production facilities and associated costs.…”
Section: Mesenchymal Stromal Cell Therapiesmentioning
confidence: 99%
“…By contrast, autologous BM-derived MSC infusion induced a significant prolongation of kidney graft survival by a T cell regulatory-dependent mechanism when a protocol biopsy showed signs of subclinical rejection and/or an increase in interstitial fibrosis/tubular atrophy 4 weeks or 6 months posttransplantation [ 61 ]. Additionally, autologous BM-derived MSC, when injected before living-related kidney transplant, led to a decrease in the circulating memory CD8 + T lymphocytes and donor-specific CD8 + T lymphocyte cytolytic response [ 62 ] and might induce tolerance [ 63 ].…”
Section: Mesenchymal Stem Cells (Mscs)mentioning
confidence: 99%